The Influence of Workload and Time Management on the Personality Competence of Elementary School Teachers in Lirik District, Indragiri Hulu Regency - Novitasari, Dian Ayu; Charlina, Charlina; Isjoni, Isjoni (Journal of Educational Sciences, 2025)
This study aims to examine the influence of two independent variables (1) workload and (2) time management on the dependent variable (3) personality competence of elementary school teachers in Lirik District, Indragiri Hulu Regency. The research employed a quantitative approach with a survey method, using questionnaires randomly distributed to 139 teachers. Descriptive analysis revealed that all three variables, workload, time management, and personality competence were rated at a very high level. This indicates that teachers in the area demonstrate strong professionalism and personal capabilities, even when facing substantial workloads. Based on the results of multiple linear regression analysis, it was found that both variables simultaneously influence teachers’ personality competence by 61,2%, while the remaining 38,8% is affected by other factors not examined in this study. These findings emphasize that effective workload management and strong time management skills are crucial factors in shaping and enhancing teachers’ personality competence. Therefore, institutional support and policies that promote work efficiency and time management skills are essential for improving the quality of education through the strengthening of teacher competence.